2005
DOI: 10.1197/jamia.m1788
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Trial of Electronic Clinical Reminders to Improve Quality of Care for Diabetes and Coronary Artery Disease

Abstract: A b s t r a c t Objective: The aim of this study was to evaluate the impact of an integrated patient-specific electronic clinical reminder system on diabetes and coronary artery disease (CAD) care and to assess physician attitudes toward this reminder system. Design:We enrolled 194 primary care physicians caring for 4549 patients with diabetes and 2199 patients with CAD at 20 ambulatory clinics. Clinics were randomized so that physicians received either evidence-based electronic reminders within their patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
249
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 223 publications
(252 citation statements)
references
References 30 publications
1
249
2
Order By: Relevance
“…Many researchers have found that although there is sufficient information to make decisions, physicians do not follow recommendations and guidelines (30,31). Some authors believe that the problem is related to the impossibility of delivering the information to the final decision maker, and tools have been developed, including electronic reminders or rewards on health care systems, with good results (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…Many researchers have found that although there is sufficient information to make decisions, physicians do not follow recommendations and guidelines (30,31). Some authors believe that the problem is related to the impossibility of delivering the information to the final decision maker, and tools have been developed, including electronic reminders or rewards on health care systems, with good results (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…Prior research has demonstrated that provider disagreement with guideline recommendations might be a significant barrier to provider guideline adherence. 18 We conducted a pragmatic randomized trial of a CDS system within academic and community-based practices providing hypertension care to a multiethnic sample of patients. Whereas we found that CDS significantly improved appropriate medication prescribing, we observed no reduction in racial and ethnic disparities in care or improvement in blood pressure control.…”
Section: Discussionmentioning
confidence: 99%
“…We selected a period of 7 days to identify medication changes that were more likely the direct result of the reminder being seen by the provider. 18 Trained abstracters then reviewed the EMR for each patient's blood pressure for the first and last hypertension-related visits during the study period to obtain participants' index and "This is a Black or elderly patient recorded as having hypertension without diabetes or heart disease, consider using a diuretic or calcium channel blocker for initial management of hypertension." B) Sample computerized reminder for uncomplicated White patient (≤65 years old) with HTN: "This is a White patient recorded as having hypertension without diabetes or heart disease, consider using a diuretic or beta-blocker for initial management of hypertension."…”
Section: Medical Record Reviewmentioning
confidence: 99%
See 2 more Smart Citations